2013
DOI: 10.1177/0306624x13503297
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Bystander-Blaming

Abstract: Contemporary victimology recognizes that an understanding of the mechanism of blaming requires a comprehensive approach that includes the victim, the offender, and the bystander. However, most of the existing research on blaming focuses on the victim and the offender, ignoring the issue of bystander-blaming. This study highlights the bystander and investigates bystander-blaming by exploring some theoretical explanations, including counterfactual thinking, defensive attribution, and gender differences. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…More recently, defensive attribution has been used to explain attributions of blame toward bystanders of sexual victimization. Levy and Ben-David (2015) used vignettes with a sample of undergraduate students in which a woman is raped by a male offender after not being accompanied by a female friend. The authors found that participants were more likely to judge the bystander who was less personally similar to them and, similar to studies examining victim blame, bystander blame was greater from male participants than female participants.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, defensive attribution has been used to explain attributions of blame toward bystanders of sexual victimization. Levy and Ben-David (2015) used vignettes with a sample of undergraduate students in which a woman is raped by a male offender after not being accompanied by a female friend. The authors found that participants were more likely to judge the bystander who was less personally similar to them and, similar to studies examining victim blame, bystander blame was greater from male participants than female participants.…”
Section: Introductionmentioning
confidence: 99%
“…Previous questionnaires for the evaluation of bystander response were used as a starting point in the design of the QIHVC (e.g., Banyard et al, 2005 , 2007 , 2014 ; Burn, 2009 ; Banyard and Moynihan, 2011 ; Coker et al, 2011 ; McMahon et al, 2014 , 2017 ; Katz et al, 2015 ; Levy and Ben-David, 2015 ; Jouriles et al, 2016 ; Cinquegrana et al, 2018 ; Gracia et al, 2018 ; Bush et al, 2019 ; Johnson et al, 2019 ; León, 2020 ; Franklin and Garza, 2021 ; León et al, 2022 ), in particular those that had defined case-scenarios (e.g., Katz et al, 2015 ; Levy and Ben-David, 2015 ; Cinquegrana et al, 2018 ; León, 2020 ; León et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…These types of tools have been widely used to study the perception of sexual assault ( Papendick and Bohner, 2017 ), and also to study bystander response in these cases. To that end, for example, Katz et al (2015) , designed a scenario to describe a high-risk situation of sexual assault in a party, alternating the variable of knowing or not knowing the victim; Levy and Ben-David (2015) presented the description of a rape, alternating the variables of age and personal circumstances of the victim at the moment of the aggression; and Franklin and Garza (2021) described an intimate encounter between two students which ended in sexual assault, alternating the variables of the relationship (how well they knew each other) between the aggressor and the victim and the victim’s skin color. Other studies of bystander response in the case of IPVAW have used various scenarios.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inasmuch as every human's suffering involves bystanders (Levy & Ben-David, 2015), community members are very potential to be one, including in the case of DV. This role as potential bystander should be empowered to prevent and to eliminate DV.…”
Section: Introductionmentioning
confidence: 99%